2018
DOI: 10.1111/jeb.13406
|View full text |Cite
|
Sign up to set email alerts
|

Neotropical frogs and mating songs: The evolution of advertisement calls in glassfrogs

Abstract: Anurans emit advertisement calls with the purpose of attracting mates and repelling conspecific competitors. The evolution of call traits is expected to be associated with the evolution of anatomical and behavioural traits due to the physics of call emission and transmission. The evolution of vocalizations might imply trade‐offs with other energetically costly behaviours, such as parental care. Here, we investigated the association between body size, calling site, parental care and call properties (call durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 117 publications
2
11
0
3
Order By: Relevance
“…This agrees with the observations of de Andrade et al (2017). Moreover, it supports the idea that the advertisement call is a multi-trait character that shows variation among species (Escalona et al 2019b), which is consistent with its utility in systematics (Köhler et al 2017). Marked differentiation of advertisement calls among closely related species is expected if the calls evolved under relatively strong evolutionary forces (e.g., reinforcement; see Pfennig & Pfennig 2009).…”
Section: Discussionsupporting
confidence: 88%
“…This agrees with the observations of de Andrade et al (2017). Moreover, it supports the idea that the advertisement call is a multi-trait character that shows variation among species (Escalona et al 2019b), which is consistent with its utility in systematics (Köhler et al 2017). Marked differentiation of advertisement calls among closely related species is expected if the calls evolved under relatively strong evolutionary forces (e.g., reinforcement; see Pfennig & Pfennig 2009).…”
Section: Discussionsupporting
confidence: 88%
“…For example, a shift to arboreal life tends to drive lineages toward an optimum size shared by most arboreal species that calls perching on vegetation (Emerson, 1991). A recent study also found that call structure (either tonal or pulsed) is related to calling site in glass frogs (Escalona Sulbarán, Simões, Gonzalez‐Voyer, & Castroviejo‐Fisher, 2019), suggesting both calling site and body size could constrain call evolution.…”
Section: Introductionmentioning
confidence: 92%
“…Lesser-used forms of continuous data may include sonic information (May-Collado, Agnarsson, and Wartzok 2007;Escalona Sulbarán et al 2019), and behavioral information (Blomberg, Garland Jr, and Ives 2003;C. R. Turner et al 2007).…”
Section: Continuous Charactersmentioning
confidence: 99%